Utilization of Cassava Peel (Manihot utilissima) Waste as an Adhesive in the Manufacture of Coconut Shell (Cocos nucifera) Charcoal Briquettes - Bayu Rudiyanto; Intan Rida Agustina; Zeni Ulma; Dafit Ari Prasetyo; Miftah Hijriawan; Bambang Piluharto; Totok Prasetyo (Center of Biomass & Renewable Energy, Diponegoro University, 2023)
Coconut shells and waste cassava peels could be used as the main raw material for biomass briquettes for alternative energy sources in Indonesia. This study aims to analyze the quality of briquettes based on a coconut shell and cassava peel adhesive through proximate analysis with three treatment ratio variations. The ratio of coconut shell to cassava peel used varied from V1 (75%:25%), V2 (70%:30%), and V3 (65%:35%). Based on the result, the charcoal briquettes produced have a density of 0.61 gram/cm³-0.66 gram/cm³, water content of 5.51%-7.85%, ash content of 1.50%-2.86%, combustion rate of 0.021 gram/s-0.026 gram/s, and the calorific value of 6,161 cal/gram-6,266 cal/gram. However, all the treatment variations appropriate the SNI 01-6235-2000, the national standard of Indonesia for the quality of charcoal briquette, which includes the calorific value (>5,000 cal/gram), moisture content (<8%), and ash content (<8%). Briquettes with the best quality were generated by V1 with a density of 0.66 gram/cm³, water content of 5.51%, ash content of 1.50%, combustion rate of 0.026 gram/s, and calorific value of 6,266 cal/gram. Furthermore, briquette material from the coconut shell waste with natural cassava peel adhesive can be feasible as an alternative fuel.